The relationship between professional quality of life and work environment among ICU nurses in Chinese: a cross-sectional study - Ni, Weiwei; Xia, Ming; Jing, Mengjuan; Zhu, Shichao; Li, Liming (Frontiers in Public Health, 2023)
Objective To explore the relationship between the professional quality of life and work environment among intensive care unit nurses, and identify the influencing factors of intensive care unit nurses' professional quality of life. Methods This study design is cross-sectional and correlational descriptive. Four hundred fourteen intensive care unit nurses from Central China were recruited. Data were collected from three questionnaires of self-designed demographic questions, the professional quality of life scale and the nursing work environment scale. Descriptive statistics, Pearson's correlation, bivariate analysis and multiple linear regression were used to analyze the data. Results A total of 414 questionnaires was collected, for an effective recovery rate of 98.57%. The original scores of the three sub-scales of professional quality of life were 33.58 ± 6.43, 31.83 ± 5.94, and 32.55 ± 5.74. Compassion satisfaction was positively correlated with the nursing working environment (p < 0.05), job burnout, and secondary trauma were negatively correlated with nursing work in environment (p < 0.05). Multiple linear regression analysis results show that, the nursing working environment entered into the influential factor model of professional quality of life scale (p < 0.001). The nursing working environment independently explained 26.9% of the changes in compassion satisfaction, 27.1% of the changes in job burnout, and 27.5% of the changes in secondary trauma. The nursing work environment is an important factor affecting the professional quality of life. Conclusion The better the nursing working environment, the higher the professional quality of life of intensive care unit nurses. Decision makers and managers can focus on improving the working environment of nurses, which may be a new perspective for managers to improve the professional quality of life of nurses and stabilize the nursing team.